2016
DOI: 10.1186/s13071-016-1716-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of mouse liver reveals a potential hepato-enteric pathogenic mechanism in acute Toxoplasma gondii infection

Abstract: BackgroundToxoplasma gondii is a worldwide spread pathogen which can infect all tissues of its host. The transcriptomic responses of infected brain and spleen have been reported. However, our knowledge of the global transcriptomic change in infected liver is limited. Additionally, T. gondii infection represents a highly dynamic process involving complex biological responses of the host at many levels. Herein, we describe such processes at a global level by discovering gene expression changes in mouse livers af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 60 publications
(56 reference statements)
8
32
2
Order By: Relevance
“…GO and KEGG pathway analyses have shown that vesicle related processes were upregulated in most infected tissues, including brain, spleen, lung and MLNs (Supplementary Files S2-S6). However, vesicle-related processes were downregulated in infected liver at 6 dpi (Supplementary File S3), which disagrees with upregulation of the vesicle-related processes detected previously in the liver of infected mice [17,44]. However, downregulation of the metabolic process of infected pig liver in the present study was also observed in the mouse model [17,44].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…GO and KEGG pathway analyses have shown that vesicle related processes were upregulated in most infected tissues, including brain, spleen, lung and MLNs (Supplementary Files S2-S6). However, vesicle-related processes were downregulated in infected liver at 6 dpi (Supplementary File S3), which disagrees with upregulation of the vesicle-related processes detected previously in the liver of infected mice [17,44]. However, downregulation of the metabolic process of infected pig liver in the present study was also observed in the mouse model [17,44].…”
Section: Discussioncontrasting
confidence: 99%
“…However, vesicle-related processes were downregulated in infected liver at 6 dpi (Supplementary File S3), which disagrees with upregulation of the vesicle-related processes detected previously in the liver of infected mice [17,44]. However, downregulation of the metabolic process of infected pig liver in the present study was also observed in the mouse model [17,44]. About 190 proteins, involved in metabolic processes, were differentially expressed in the infected livers, most of them downregulated (Supplementary File S3).…”
Section: Discussioncontrasting
confidence: 87%
“…More recently, He et al (2016b) analyzed the transcriptomic changes in the spleen of infected mice to elucidate the immune responses against T. gondii infection. Later, they evaluated the transcriptomic gene expressions in the liver of infected mice during the early stages of T. gondii infection (He et al, 2016a). However, data on the global transcriptomic changes in uterine tissues of mouse with acute T. gondii infection are highly deficient, despite of its crucial importance.…”
Section: Introductionmentioning
confidence: 99%
“…RNa-seq data in liver in infection with PYS (type I/III) parasites (data from He et al [14]). Panel A–extract from cholesterol biosynthetic pathway and export (adapted from KEGG pathways).…”
Section: Resultsmentioning
confidence: 99%